2021
DOI: 10.1152/ajpheart.00736.2020
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced cognitive impairment in older adults: a microvascular perspective

Abstract: Over two thirds of individuals aged 65 and older are obese or overweight in the United States. Epidemiological data show an association between the degree of adiposity and cognitive dysfunction in the elderly. In this review, the pathophysiological roles of microvascular mechanisms, including impaired endothelial function and neurovascular coupling responses, microvascular rarefaction and blood-brain barrier disruption in the genesis of cognitive impairment in geriatric obesity are considered. The potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 325 publications
1
44
0
1
Order By: Relevance
“…Several studies have shown that obesity and high dietary fat intake are associated with increased risk of neuropsychiatric, cognitive and neurodegenerative disorders [ 9 , 164 , 165 , 166 ]. Meta-analysis studies showed that individuals with obesity or associated metabolic disorders in midlife have a significantly higher risk for development of dementia or AD later in life [ 164 , 167 , 168 ].…”
Section: Obesity and Risk Of Neurological Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that obesity and high dietary fat intake are associated with increased risk of neuropsychiatric, cognitive and neurodegenerative disorders [ 9 , 164 , 165 , 166 ]. Meta-analysis studies showed that individuals with obesity or associated metabolic disorders in midlife have a significantly higher risk for development of dementia or AD later in life [ 164 , 167 , 168 ].…”
Section: Obesity and Risk Of Neurological Diseasementioning
confidence: 99%
“…Meta-analysis studies showed that individuals with obesity or associated metabolic disorders in midlife have a significantly higher risk for development of dementia or AD later in life [ 164 , 167 , 168 ]. Moreover, numerous studies support a clear link between obesity and cognitive decline [ 165 , 169 , 170 , 171 ]. Obesity-associated comorbidities, including hypertension, type 2 diabetes mellitus and dyslipidemia, can further augment cognitive impairment [ 165 ].…”
Section: Obesity and Risk Of Neurological Diseasementioning
confidence: 99%
See 3 more Smart Citations